Calcified abdominal pregnancy with eighteen years of evolution: case report - Passini Júnior, Renato; Knobel, Roxana; Parpinelli, Mary Ângela; Pereira, Belmiro Gonçalves; Amaral, Eliana; Surita, Fernanda Garanhani de Castro; Lett, Caio Rogério de Araújo (São Paulo Medical Journal, 2000)
CONTEXT: The lithopedion (calcified abdominal pregnancy) is a rare phenomenon and there are less than 300 cases reported in the medical literature. CASE REPORT: In this case, a 40 year-old patient had had her only pregnancy 18 years earlier, without medical assistance since then. She came to our hospital with pain and tumoral mass of approximately 20 centimeters in diameter. Complementary examinations (abdominal X-ray, ultrasonography and computerized tomography) demonstrated an extra-uterine abdominal 31-week pregnancy with calcification areas. Exploratory laparotomy was performed, with extirpation of a well-conserved fetus with partially calcified ovular membranes.